Identity Creation and Resource Controlling Strategies: Thoughts on Edomite Ethnogenesis and Development - Maʾir, Aharon (Bulletin of ASOR, 2021)
In this paper I suggest that the evolution of the control of natural resources and trade routes in the Arabah Valley and its environs was the basis for the formation of Edomite identity in the early Iron Age. Building on insights on ethnogenesis in Southeast Asia in the studies of Joseph Scott and James Warren, I attempt to align this with recent discussions on early Edom, and the role that this group played in the regional economic web of the Iron Age.